Alloy steel and high austenitizing starting temperature brake disc made of same

By regulating the composition and smelting process of alloy steel, an alloy steel brake disc with high temperature strength and thermal fatigue resistance was prepared, which solved the problem of the strength drop and thermal fatigue of the brake disc at high temperatures, and significantly improved the service life of the brake disc.

CN119800223APending Publication Date: 2025-04-11CHINA STATE RAILWAY GRP CO LTD +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510035295.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The strength of the brake disc of the high-speed train decreases at high temperatures, which is prone to thermal fatigue, resulting in failure of fractures, and insufficient high-temperature strength and thermal fatigue resistance of existing materials.

Method used

By regulating the composition of alloy steel, the content of elements such as C, Mn, Si, Cr, Ni, Mo, Nb, V, Cu, Al is increased, and the lanthanides are added, and the alloy steel brake disc is prepared by medium-frequency induction furnace smelting and casting technology is used to prepare the alloy steel brake disc to improve its high temperature strength and thermal fatigue resistance.

Benefits of technology

The brake disc maintains high material strength and tissue stability at high temperatures, improves fatigue resistance and service life, and avoids thermal crack failure problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235370160000061
    Figure BDA0005235370160000061
Patent Text Reader

Abstract

The invention provides alloy steel and a high austenitizing starting temperature brake disc made of the alloy steel. The alloy steel comprises the following components in percentage by weight: 0.15%-0.35% of C, 0.7%-1.4% of Mn, 0.3%-0.8% of Si, 0.8%-1.6% of Cr, 0.6%-1.3% of Ni, 0.4%-1.2% of Mo, less than or equal to 0.3% of Nb, 0.1%-0.4% of V, less than or equal to 0.2% of Cu, less than or equal to 0.6% of Al and the balance of Fe and inevitable impurity elements. The cast steel brake disc manufactured by using the alloy steel provided by the invention can ensure better mechanical performance under a high-speed braking condition; higher material strength and structure stability are kept at higher temperature; and the high Ac1 is achieved, austenite phase change caused by temperature rise in the braking process can be avoided to a great extent, and therefore the better anti-fatigue performance and the longer service life are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, in particular to an alloy steel and a high austenitization start temperature brake disc made of the alloy steel. Background Art

[0002] High-speed train brake discs usually work under complex working conditions such as strong friction, high heat load, large braking force and centrifugal force. The reliability of the brake disc almost determines the reliability level of the entire basic braking device, which directly affects the driving safety of the train.

[0003] As the speed of trains increases, the braking load and heat energy increase exponentially, which will inevitably cause abnormal hot spots in the local area of ​​the brake disc. The strength of the brake disc material will drop sharply at high temperatures, which can easily lead to thermal fatigue after repeated braking, and in severe cases, the entire brake disc may break and fail. Therefore, good high-temperature strength and thermal fatigue resistance are important criteria for selecting brake disc materials.

[0004] At present, high-speed train brake discs are mainly made of ordinary quenched and tempered cast steel, which has insufficient high-temperature strength and thermal fatigue resistance, and no research and development work has been seen so far on brake discs with good high-temperature strength and thermal fatigue resistance. Therefore, in order to solve the problem of insufficient high-temperature strength and thermal fatigue resistance of brake discs at higher train speeds, it is necessary to provide an alloy steel brake disc with good high-temperature strength, austenitization start temperature (Ac1) and thermal fatigue resistance. Summary of the invention

[0005] In order to solve the above technical problems, the object of the present invention is to provide an alloy steel and a high austenitizing start temperature brake disc made of the alloy steel. By regulating the composition of the alloy steel, the brake disc made of the alloy steel has excellent high temperature strength and thermal fatigue resistance, as well as a higher austenitizing start temperature (Ac1).

[0006] To achieve the above-mentioned purpose, the present invention provides an alloy steel, wherein, by mass percentage, the composition of the alloy steel comprises: C: 0.15%-0.35%, Mn: 0.7%-1.4%, Si: 0.3%-0.8%, Cr: 0.8%-1.6%, Ni: 0.6%-1.3%, Mo: 0.4%-1.2%, Nb: ≤0.3%, V: 0.1%-0.4%, Cu: ≤0.2%, Al: ≤0.6%, and the rest are Fe and unavoidable impurity elements.

[0007] According to a specific embodiment of the present invention, preferably, the composition of the alloy steel comprises, by mass percentage: C: 0.17%-0.3%, Mn: 0.7%-1.4%, Si: 0.3%-0.8%, Cr: 0.8%-1.6%, Ni: 0.6%-1.3%, Mo: 0.6%-1.2%, Nb: ≤0.3%, V: 0.1%-0.4%, Cu: ≤0.2%, Al: ≤0.6%, and the rest is Fe and unavoidable impurity elements.

[0008] According to a specific embodiment of the present invention, preferably, the composition of the alloy steel comprises, by mass percentage: C: 0.17%-0.3%, Mn: 0.8%-1.3%, Si: 0.3%-0.7%, Cr: 0.9%-1.4%, Ni: 0.6%-1.1%, Mo: 0.6%-1.0%, Nb: ≤0.2%, V: 0.15%-0.27%, Cu: ≤0.2%, Al: ≤0.3%, and the rest is Fe and unavoidable impurity elements.

[0009] According to a specific embodiment of the present invention, preferably, the composition of the alloy steel comprises, by mass percentage: C: 0.23%-0.24%, Mn: 0.91%-0.94%, Si: 0.59%-0.63%, Cr: 0.96%-0.98%, Ni: 0.9%-0.91%, Mo: 0.84%-0.86%, Nb: 0.14%-0.17%, V: 0.23%-0.25%, Cu: 0.14%-0.17%, Al: 0.03%-0.04%, and the rest is Fe and unavoidable impurity elements.

[0010] According to a specific embodiment of the present invention, preferably, the composition of the alloy steel further comprises, by mass percentage, lanthanide elements (Ln) ≤ 0.03%, more preferably lanthanide elements: 0.02%.

[0011] According to a specific embodiment of the present invention, preferably, the lanthanide element includes one or a combination of two or more of lanthanum (La), cerium (Ce), yttrium (Y), etc.

[0012] The purpose of the present invention is to use C-Mn-Si-Cr-Ni as the alloy composition basis, add appropriate amounts of Mo, V elements and lanthanide elements (Ln), use second phase strengthening, fine grain strengthening and grain boundary purification and other strengthening means to improve the high temperature strength of the material, and increase the Ac1 temperature of the material by adjusting the content of elements such as Ni, Cr, Mo, V, etc., so that the brake disc has better thermal fatigue resistance, which is beneficial to improving the service life of the brake disc.

[0013] In the present invention, the properties of each element are as follows, wherein the content is in mass percentage:

[0014] Carbon: Carbon is the main element that affects the structure and performance of steel. It has the function of strengthening solid solution and improving hardenability. As the carbon content increases, the strength of steel increases, while the plasticity and toughness decrease. When the carbon content is lower than 0.15%, the hardenability and strength of steel deteriorate, which is not conducive to the consistency of performance of large castings such as brake discs, and needs to be compensated by the addition of other alloying elements; however, when the carbon content is higher than 0.35%, it is easy to cause a large amount of brittle cementite to precipitate, which is not conducive to the plasticity and toughness of steel. Therefore, the appropriate carbon content is 0.15%-0.35%;

[0015] Manganese: It has a significant effect on increasing hardenability and solid solution strengthening, and is easy to obtain martensite structure, which can improve the strength, hardness and wear resistance of steel. However, manganese has a significant tendency to segregate. If the manganese content is too high, it is easy to reduce toughness and may produce too much residual austenite, increase the overheating sensitivity of steel, and reduce wear resistance. Therefore, the appropriate manganese content is 0.7%-1.4%;

[0016] Silicon: It significantly improves the hardenability of steel and plays a role in solid solution strengthening, improving the strength and hardness of steel. At the same time, it can inhibit the precipitation of carbides, improve tempering resistance, and inhibit the occurrence of the first type of temper brittleness. In addition, it can also increase the Ac1 temperature of steel and improve the thermal fatigue resistance of steel. When its content is lower than 0.3%, the above effects are not obvious; when its content is higher than 0.8%, it will damage the toughness and fatigue performance of steel. Therefore, the appropriate silicon content is 0.3%-0.8%;

[0017] Chromium: It increases the hardenability of steel and solid solution strengthening, which can improve the strength and hardness of steel. Cr is a carbide-forming element, which will form alloy carbides in steel, which can refine grains and improve tempering stability. However, too high a content will cause poor thermal conductivity, form coarse dendrites, etc., increase the tendency of castings to crack, and promote tempering brittleness. Therefore, the appropriate chromium content is 0.8%-1.6%;

[0018] Nickel: It can improve the strength of steel, especially the yield strength, while having little damage to the plasticity and toughness of steel. In addition, it can also improve fatigue resistance, reduce notch sensitivity and ductile-brittle transition temperature. When its content is lower than 0.6%, the above effects are not obvious; however, when the nickel content is higher than 1.3%, the improvement effect is not obvious, and the alloy cost increases significantly. Therefore, the appropriate nickel content is 0.6%-1.3%;

[0019] Molybdenum: It can significantly improve the high temperature strength and Ac1 temperature of steel. It is one of the core elements of high temperature resistant brake discs. It also has the functions of improving hardenability, tempering stability, and grain refinement. It can change the grade morphology and distribution of carbides, eliminate or reduce temper brittleness, and inhibit the transformation of supercooled austenite to pearlite, making the steel have higher toughness. However, it is expensive. Therefore, the appropriate molybdenum content is 0.4%-1.2%;

[0020] Niobium: Niobium partially dissolves into solid solution, playing a role of solid solution strengthening. When dissolved into austenite, it significantly improves the hardenability of steel. However, when it exists in the form of carbides, it can refine the grains, improve the impact toughness of steel and reduce the brittle transition temperature. However, when the niobium content is greater than 0.3%, the improvement effect is not obvious.

[0021] Vanadium: Vanadium exists in steel mainly in the form of carbides, and its main function is to refine grains and improve tempering stability and high-temperature strength. However, when its content is greater than 0.4%, the effect of improving performance begins to be insignificant, and the tempering resistance is greatly improved. When the content is less than 0.1%, the effect of improving high-temperature strength is not obvious. Therefore, the appropriate vanadium content is 0.1%-0.4%;

[0022] Copper element: can improve the strength and yield strength ratio of steel, and can also improve the atmospheric corrosion resistance of steel. However, when the content is too high, it is not conducive to hot deformation processing and copper brittleness may occur. Therefore, in the alloy steel provided by the present invention, the copper content is controlled to be ≤0.2%;

[0023] Aluminum: mainly used for deoxidation and grain refinement, and also plays a role in solid solution strengthening and improving Ac1. However, too high a content may lead to an increase in inclusions. In the alloy steel provided by the present invention, the aluminum content is controlled to be ≤0.6%;

[0024] Lanthanide elements: mainly used to purify grain boundaries; lanthanide elements can make the sulfur and oxygen elements present in the steel form ferrous sulfide and ferrous oxide with iron, and further make the ferrous sulfide and ferrous oxide reach saturation due to the reduction of solubility during the solidification process of the steel, and precipitate at the grain boundaries, thereby purifying the steel grains; however, the cost of lanthanide elements is relatively high, therefore, the appropriate lanthanide content is ≤0.03%.

[0025] According to a specific embodiment of the present invention, preferably, the alloy steel is prepared by an alloy smelting process; the alloy steel smelting process commonly used in the art can be used.

[0026] According to a specific implementation scheme of the present invention, preferably, the alloy smelting process is a medium frequency induction furnace smelting process; the process parameters in the specific smelting process can be determined according to the existing smelting process.

[0027] Among them, the medium frequency induction furnace smelting process can include the following steps: charging (among which, the non-oxidizable charge is directly charged into the electric furnace, and the easily oxidizable charge is added in batches during the smelting process according to the process requirements), melting (using high power to quickly melt the charge), and casting steel ingots.

[0028] In the present invention, a qualified master alloy can be obtained through a medium frequency induction furnace smelting process, which meets the requirements for manufacturing brake discs; and the alloy produced by the medium frequency induction furnace has uniform composition, basically has no metallurgical defects such as shrinkage, looseness, segregation, etc., and the casting material utilization rate can reach more than 85%, thereby improving the performance of the alloy steel.

[0029] The present invention also provides a high austenitization start temperature brake disc, which is made of the alloy steel.

[0030] According to a specific embodiment of the present invention, preferably, the brake disc is manufactured by a casting process.

[0031] In the present invention, after the mother alloy of the present invention is prepared, the brake disc can be manufactured using a casting process commonly used in the art, for example, the following casting process flow: casting position design, fractal surface design, shrinkage design, machining allowance design, casting system design, riser, chill, and rib design, mold design and manufacturing, molding, core making, sand mold heating, and casting.

[0032] According to a specific embodiment of the present invention, preferably, the cast brake disc is subjected to normalizing pretreatment and quenching and tempering treatment.

[0033] According to a specific embodiment of the present invention, preferably, the normalizing pretreatment and tempering treatment include: keeping the cast brake disc at 920-980°C for 2-4h, and then normalizing to room temperature; heating the normalized brake disc to 920-980°C and keeping it for 2-4h, and then quenching to room temperature; heating the quenched brake disc to 630-660°C for tempering treatment for 3-4h, and then air cooling to room temperature.

[0034] In the present invention, after the brake disc of the present invention is cast, a commonly used alloy steel heat treatment process in the art may be used, such as a normalizing pretreatment and a quenching and tempering treatment process. The process parameters in the specific heat treatment process may also be determined according to the existing heat treatment process.

[0035] According to a specific embodiment of the present invention, preferably, the brake disc is a brake disc for a rail transit vehicle.

[0036] According to a specific embodiment of the present invention, preferably, the brake disc is a brake disc for high-speed trains.

[0037] According to a specific embodiment of the present invention, preferably, the speed of the high-speed train is 300-450 km / h, more preferably 441-450 km / h, and further preferably 450 km / h.

[0038] According to a specific embodiment of the present invention, preferably, the austenitization start temperature of the brake disc is 810° C. or higher, more preferably 814° C. or higher.

[0039] The key of the present invention is to provide an alloy steel for brake discs with good high temperature strength and Ac1 temperature, and a brake disc made of such alloy steel. The smelting of the alloy steel and the manufacture and heat treatment of the brake disc can be carried out according to conventional processes in the art. For example, when using cast alloy steel to manufacture brake discs for high-speed trains, existing casting and heat treatment equipment for high-speed brake discs can be used.

[0040] When working under complex working conditions such as strong friction, high heat load, large braking force and centrifugal force, the brake disc provided by the present invention can meet the requirements of the above working conditions for the safety performance of the brake disc. For example, when braking at a speed of 450km / h, the brake disc of the present invention can work stably and normally, maintain a relatively stable friction coefficient, and will not have thermal crack failure problems.

[0041] Compared with other brake discs, the cast steel brake disc made of the alloy steel provided by the present invention has the following advantages:

[0042] (1) Better mechanical performance under high-speed braking conditions;

[0043] (2) Maintaining higher material strength and organizational stability at higher temperatures;

[0044] (3) With a higher Ac1, the austenite phase transformation caused by temperature rise during braking can be avoided to a large extent, and the probability of fatigue crack initiation and the growth rate of fatigue crack can be reduced, thereby having better fatigue resistance and longer service life. DETAILED DESCRIPTION

[0045] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0046] The alloy steels given in the following embodiments and comparative examples are all obtained by smelting in the induction furnace provided by the present invention and undergoing a quenching and tempering process heat treatment. The corresponding brake discs are made by a casting process and undergo the following normalizing pretreatment and quenching and tempering process flow:

[0047] The cast brake disc was kept at 950°C for 3 hours and then normalized to room temperature;

[0048] The normalized brake disc is heated to 930℃ and kept at this temperature for 3h, then quenched to room temperature;

[0049] The quenched brake disc was heated to 640°C and kept at this temperature for 4 h, and then air-cooled to room temperature.

[0050] Table 1 shows the composition (mass percentage) of the alloy steel brake disc in the following embodiments and comparative examples, and the balance is iron and inevitable impurity elements.

[0051] Table 1. Composition and content of alloy steel brake disc in each embodiment and comparative example (mass percentage, %)

[0052] C Mn Si Cr Ni Mo Nb V Cu Al La B Example 1 0.23 0.94 0.63 0.98 0.91 0.86 0.14 0.25 0.14 0.04 0.02 / Example 2 0.24 0.91 0.59 0.96 0.90 0.84 0.17 0.23 0.17 0.03 / / Comparative Example 1 0.22 0.84 0.98 0.50 0.81 0.76 0.14 0.30 0.19 0.03 / 0.003

[0053] Test Example 1

[0054] This test example conducts mechanical property test on the brake discs in Examples 1-2 and Comparative Example 1. The specific process and results are as follows:

[0055] Standard tensile specimens were taken from the friction surface of the brake disc, and the mechanical properties at room temperature and the high temperature strength at 600°C and 700°C of the brake discs made of the alloy steel of Examples 1-2 and Comparative Example 1 were measured using a universal tensile testing machine in accordance with GB / T 228 “Tensile test for metallic materials” and GB / T 229 “Charpy pendulum impact test method for metallic materials”, as shown in Table 2.

[0056] Table 2. Mechanical properties of alloy steel brake discs in various embodiments and comparative examples

[0057]

[0058] It can be seen from Table 2 that at room temperature, the tensile strength R m >1220MPa, yield strength R p0.2 >1130MPa, elongation A>12%, impact energy A kv2 >70J; at 600℃, tensile strength R m >610MPa, yield strength R p0.2 >530MPa; This shows that the alloy steel brake disc prepared by the present invention has good high temperature strength and Ac1 temperature.

[0059] Furthermore, at a higher temperature of 700°C, the tensile strength R of the brake disc of the present invention is m >330MPa, yield strength R p0.2 >250MPa, still has high strength and good plasticity.

[0060] By comparing the test results of Example 1 and Example 2, it can be seen that the addition of La element further improves the high-temperature strength of the brake disc, showing better thermal fatigue resistance.

[0061] Therefore, by regulating the element composition and proportion in the alloy steel, compared with the comparative example 1 of the brake disc made of existing materials, the embodiments 1-2 provided by the present invention have higher high temperature strength and better plasticity.

[0062] Test Example 2

[0063] This test example tests the austenitization start temperature of the brake discs in Examples 1-2 and Comparative Example 1. The specific process and results are as follows:

[0064] A linear thermal expansion standard sample was taken from the friction surface of the brake disc, and the austenitization start temperature of the brake discs made of the alloy steel of Examples 1-2 and Comparative Example 1 was measured respectively by a linear thermal expansion tester in accordance with GB / T4339 "Determination of characteristic parameters of thermal expansion of metallic materials".

[0065] Table 3. Austenitization start temperature and complete austenitization temperature of alloy steel brake disc in each embodiment and comparative example

[0066] Austenitizing start temperature Ac1 / ℃ Complete austenitizing temperature Ac3 / ℃ Example 1 816 903 Example 2 814 900 Comparative Example 1 782 901

[0067] For brake discs, the value and difficulty of increasing the Ac1 temperature is much higher than the Ac3 temperature, because once the temperature exceeds the Ac1 temperature, austenitization transformation may occur. Therefore, brake discs with higher Ac1 temperatures need to have better high temperature resistance. As shown in Table 3, the Ac3 temperatures of Examples 1-2 and Comparative Example 1 are basically similar, both of which are high temperatures above 900°C. However, the Ac1 temperature of Comparative Example 1 is much different from that of Examples 1-2.

[0068] Therefore, the present invention regulates the element composition and proportion in the alloy steel so that the alloy steel brake disc can maintain a relatively high Ac3 temperature while having good high temperature strength and Ac1 temperature. Its austenitization start temperature can reach above 810°C, which is significantly higher than the Ac1 temperature of the brake disc in comparative example 1.

[0069] Test Example 3

[0070] This test example is a test conducted on a 1:1 brake power test bench in accordance with the relevant requirements of UIC541-3 using the brake disc composed of the alloy steel in Example 1. The specific process and results are as follows:

[0071] Test condition 1: wheel diameter is 890mm, brake disc load is 4t, brake pad pressure is 10kN×2, friction radius is 247, initial braking speed is 450km / h, actual braking distance is 7195m, and the experimentally measured average friction coefficient of the brake disc is 0.407.

[0072] Test condition 2: The wheel diameter is 890mm, the brake disc load is 4t, the brake pad pressure is 15kN×2, the friction radius is 247, the initial braking speed is 450km / h, the actual braking distance is 5920m, and the experimentally measured average friction coefficient of the brake disc is 0.349.

[0073] The test results show that the friction coefficient between the brake disc and the matched friction pair in Example 1 is stable, there are no hot spots or thermal cracks on the surface of the brake disc, and there is no obvious wear phenomenon.

[0074] Test Example 4

[0075] This test example is a fatigue test conducted on a 1:1 brake power bench using a brake disc composed of the alloy steel of Example 1 and a brake disc composed of the alloy steel of Comparative Example 1. The specific process and results are as follows:

[0076] Test conditions: wheel diameter is 890mm, brake disc load is 4t, brake pad pressure is 10kN×2, friction radius is 247, initial braking speed is 450km / h, cycle is 1000 times, and brake disc wear is measured every 100 times.

[0077] Table 4. Fatigue wear of brake discs composed of alloy steels of Example 1 and Comparative Example 1

[0078] Average wear per 100 braking times / mm Example 1 0.16 Comparative Example 1 0.18

[0079] It can be seen from Table 4 that under the same braking conditions, the brake disc composed of the alloy steel of Example 1 has lower average wear than the brake disc composed of the alloy steel of Comparative Example 1 and has a longer service life.

Claims

1. An alloy steel, wherein: The composition of the alloy steel comprises, by mass percentage: C: 0.15%-0.35%, Mn: 0.7%-1.4%, Si: 0.3%-0.8%, Cr: 0.8%-1.6%, Ni: 0.6%-1.3%, Mo: 0.4%-1.2%, Nb: ≤0.3%, V: 0.1%-0.4%, Cu: ≤0.2%, Al: ≤0.6%, the rest are Fe and unavoidable impurity elements.

2. The alloy steel according to claim 1, wherein: The composition of the alloy steel comprises, by mass percentage: C: 0.17%-0.3%, Mn: 0.7%-1.4%, Si: 0.3%-0.8%, Cr: 0.8%-1.6%, Ni: 0.6%-1.3%, Mo: 0.6%-1.2%, Nb: ≤0.3%, V: 0.1%-0.4%, Cu: ≤0.2%, Al: ≤0.6%, and the rest are Fe and unavoidable impurity elements.

3. The alloy steel according to claim 1, wherein: The composition of the alloy steel comprises, by mass percentage: C: 0.17%-0.3%, Mn: 0.8%-1.3%, Si: 0.3%-0.7%, Cr: 0.9%-1.4%, Ni: 0.6%-1.1%, Mo: 0.6%-1.0%, Nb: ≤0.2%, V: 0.15%-0.27%, Cu: ≤0.2%, Al: ≤0.3%, the rest are Fe and unavoidable impurity elements.

4. The alloy steel according to claim 1, wherein: The composition of the alloy steel comprises, by mass percentage: C: 0.23%-0.24%, Mn: 0.91%-0.94%, Si: 0.59%-0.63%, Cr: 0.96%-0.98%, Ni: 0.9%-0.91%, Mo: 0.84%-0.86%, Nb: 0.14%-0.17%, V: 0.23%-0.25%, Cu: 0.14%-0.17%, Al: 0.03%-0.04%, and the rest are Fe and unavoidable impurity elements.

5. The alloy steel according to any one of claims 1 to 4, wherein: The alloy steel further comprises, by mass percentage, lanthanide elements: ≤0.03%, preferably lanthanide elements: 0.02%; Preferably, the lanthanide element includes one or a combination of two or more of lanthanum, cerium and yttrium.

6. A high austenitizing start temperature brake disc made of the alloy steel according to any one of claims 1 to 5.

7. The high austenitizing start temperature brake disc according to claim 6, wherein: The brake disc is manufactured by a casting process; Preferably, the cast brake disc is subjected to normalizing pretreatment and quenching and tempering treatment; More preferably, the normalizing pretreatment and quenching and tempering treatment include: The cast brake disc is kept at 920-980°C for 2-4 hours and then normalized to room temperature; Heat the normalized brake disc to 920-980℃ and keep it at that temperature for 2-4h, then quench it to room temperature; The quenched brake disc is heated to 630-660℃ and tempered for 3-4h, then air-cooled to room temperature.

8. The high austenitizing start temperature brake disc according to claim 6, wherein: The brake disc is a brake disc for rail transit vehicles; Preferably, the brake disc is a brake disc for high-speed trains.

9. The high austenitizing start temperature brake disc according to claim 8, wherein: The speed of the high-speed train is 300-450 km / h, preferably 441-450 km / h, and more preferably 450 km / h.

10. The high austenitizing start temperature brake disc according to claim 6, wherein: The austenitization start temperature of the brake disc is 810° C. or higher, preferably 814° C. or higher.

Citation Information

Cited By

  • High-temperature-resistant thermal-fatigue-resistant martensitic steel and preparation method thereof

    CN121737570A